Social-Cultural Aspect of Stunting: A Systematic Review - Suhardin, Saverinus; Indarwati, Retno; Meo, Christina Marina; Sari, Ni Ketut Putri Martha; Halimatunnisa, Maulin X (International Journal of Psychosocial Rehabilitation, 2020)
Stunting is a priority concern in developing countries because it harms children's health and development. The WHO’s conceptual framework for stunting states that socio-culture is one of the factors causing it. The purpose of this systematic review was to summarize the previous studies that provide an overview related to the socio-cultural aspects of the incidence of stunting. This systematic review used the guidance from the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). The article search was carried out using 8 databases (Scopus, ProQuest, Springerlink, ScienceDirect, PubMed, SAGE, Medline and CINHAL) with the help of Boolean Operators and keywords such as culture OR culture OR "cultural beliefs" OR transcultural OR "growth disorder" OR stunted OR stunting. The initial findings totaled 430,679 documents. There were 24 studies included in the review after they were limited by the criteria for the study such as being published between 2015 and 2020. Other criteria were that they were English-language articles, journal articles, that the children’s age ranged from birth to 5 years and that they used the interview method in their study to explore the socio-cultural picture related to stunting. The analysis of the findings from each study was grouped according to the 4 main themes: nutritional practices, family support systems, views on stunting and the barriers to providing interventions. This covers the socio-cultural aspects related to stunting. This systematic review has limitations such as where all of the information recorded was done so using the interview method or an FGD. This means that the participants may give answers that they think are the most generally accepted rather than the truth. The results of the study form the basis for the development of socio- based stunting care.